2006
DOI: 10.1007/s10725-006-9001-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spermidine and spermine levels on salt tolerance associated with tonoplast H+-ATPase and H+-PPase activities in barley roots

Abstract: The effects of polyamines (PutrescinePut; Spermidine-Spd; and Spermine-Spm) on salt tolerance of seedlings of two barley (Hordeum vulgare L.) cultivars (J4, salt-tolerant; KP7, salt-sensitive) were investigated. The results showed that, the salt-tolerant cultivar J4 seedlings accumulated much higher levels of Spd and Spm and lower Put than the salt-sensitive cultivar KP7 under salt stress. At the same time, the dry weight of KP7 decreased significantly than that of J4. After methylglyoxal bis(guanylhydrazone) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…Under natural conditions, PA may also play a beneficial role in mycorrhizal development, contributing to improved plant water status and water use efficiency (Wu et al, 2010). Second, in many cases accumulation of PAs positively correlates with salt (Chattopadhayay et al, 2002; Liu et al, 2006; Mutlu and Bozcuk, 2007) and drought (van der Mescht et al, 1998; Liu et al, 2005), resistance. Third, and maybe the strongest line of evidence came from the experiments with the gain- or loss-of-the-function mutants.…”
Section: Stress-induced Changes In Polyamine Content and Their Role Imentioning
confidence: 99%
“…Under natural conditions, PA may also play a beneficial role in mycorrhizal development, contributing to improved plant water status and water use efficiency (Wu et al, 2010). Second, in many cases accumulation of PAs positively correlates with salt (Chattopadhayay et al, 2002; Liu et al, 2006; Mutlu and Bozcuk, 2007) and drought (van der Mescht et al, 1998; Liu et al, 2005), resistance. Third, and maybe the strongest line of evidence came from the experiments with the gain- or loss-of-the-function mutants.…”
Section: Stress-induced Changes In Polyamine Content and Their Role Imentioning
confidence: 99%
“…Some works suggested that PAs play a role in the modification of the activities of the proton pumps in plants, especially under stresses conditions (Mornet et al , Liu et al , Liu et al , Garufi et al , Janicka‐Russak et al ). It was postulated that PAs contribute to the ionic equilibrium due to their polycationic nature, being beneficial for root development under salt stress (Janicka‐Russak et al ).…”
Section: Introductionmentioning
confidence: 99%
“…increased, so the action of PAs contributed to ionic equilibrium. A salt-tolerant barley cultivar accumulated in the roots much higher levels of Spm and Spm and a lower Put content than the salt-sensitive cultivar under salt stress (Liu et al 2006). It has often been suggested that Spd and Spm may contribute to stress tolerance, while Put has a lower or no effect on it (Bouchereau et al 1999;Liu et al 2007).…”
Section: Discussionmentioning
confidence: 99%